2015
DOI: 10.5901/mjss.2015.v6n6s4p469
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment, Expectations, Priorities and Attitudes Toward Development

Abstract: The main objective of this study is to examine the empowerment, expectation, priorities and attitudes toward development among rural community in Malaysia. This study is quantitative in nature and a total of 900 respondents from three states in Peninsular Malaysia were involved. This study has found that the rural communities were very well aware of the needs for local development and exhibited high expectations on its life-changing outcomes. The findings showed high rural community's involvement in decision m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…However, students' willingness to practice environmental practices is still low. The findings of this study are in line with the study of Abu Samah (2008) who stated that students have a good awareness of environmental problems but this awareness is not translated into actual practice.…”
Section: Literature Reviewsupporting
confidence: 84%
“…However, students' willingness to practice environmental practices is still low. The findings of this study are in line with the study of Abu Samah (2008) who stated that students have a good awareness of environmental problems but this awareness is not translated into actual practice.…”
Section: Literature Reviewsupporting
confidence: 84%
“…This implies that the rural youths find Facebook useful to feel connected even among close friends and its access usage through multiple gadgets have assisted in their frequent use of Facebook. The multiplicity of digital communication could in fact heighten the rural youth community's attitudes to engage in community development by empowering them through the use of Facebook, just as Abu Samah et al (2015) have mentioned that the rural communities are ready for local development, but they highly need support from the Village Development and Security Committees (JKKK) to enforce the use of digital technology. Therefore, it is recommended that Facebook be used as a medium to empower the village community by getting the relevant parties to involve as they mostly befriended people who they encounter daily on Facebook.…”
Section: Facebook Group Functionalitymentioning
confidence: 99%
“…Some youths cannot afford monthly internet subscriptions; therefore, the Malaysian government established 1Malaysia Wireless Village Programme in 2011 with the support from Universal Service Provision (USP). The provision of internet and the diffusion of innovation as mentioned by Abu Samah et al (2015), could aid in rural empowerment as the community's awareness of self-development is high, however, their knowledge regarding community building was still low. Scholars have suggested that the use of technology could benefit rural youths in community building and social bonding.…”
Section: Introductionmentioning
confidence: 99%